The Shephard Type Problems for General $L_p$-Centroid Bodies (Communications in Mathematical Research, 2020)
In this paper, combining with the $L_p$-dual geominimal surface area and the general $L_p$-centroid bodies, we research the Shephard type problems for general $L_p$-centroid bodies.